The Role of Decisions in Intervening Website Quality, e-Promotion, and e-Trust towards e-Repurchase Intention on e-Commerce - Hamdan, Hamdan; Imaningsih, Erna Sofriana; Indrajaya, Sonny; Raharja, Indra; Yuliantini, Tine (Universitas Mercu Buana, 2023)
Objectives: This study aims to analyze decisions as a mediating factor of website quality, e-promotion, and e-trust on the e-repurchase intention at Shopee online shop. An important occurrence to be studied during the pandemic is the phenomenon of online shopping behavior. Methodology: The analysis method used in this study is a quantitative approach with the PLS-SEM data analysis method because it is predictive and able to produce a model with a good test level. The population of this research are consumers in Jakarta through the selection of purposive sampling. The sample obtained according to the criteria is 262 respondents who are accepted and eligible for testing.Finding: Online shopping decisions affect repurchase intentions while website quality does not but decision acts as a mediator. Promotion does not affect the decision and repurchase intention and decisions do not act as a mediator. Trust affects decisions and repurchase intentions, and decisions can act as mediators, although trust has a stronger influence on repurchase intentions directly. Conclusion: Decisions give the best role in intervening with website quality and repurchase intentions, but directly website quality does not result in the repurchase. Although the decision does not provide the best role as a promotional mediator with direct or indirect repurchase intentions. In contrast, decisions as a trusted mediator ensure the occurrence of very strong repurchase intentions either directly or indirectly. In addition, this model contributes to e-commerce players, information system developers, and managers as a consideration in implementing strategic decision-making. The differences in the findings and shortcomings of this study are gaps that will become an important study in the context of online shopping behavior, especially the study of promotion which is inversely related to trust and research phenomena